Effect of substrate concentration and ph on succinic acid production - Nik Nor Aziati, Abd Aziz (2010)
The purpose of this research is to study the effect of substrate concentration and pH on succinic acid production. Succinic acid has been produced from the fermentation process by using Escherichia coli b-strain. The experiments were conducted in Modified Schott Bottle in incubator shaker to maintain anaerobic condition, temperature and agitation speed. Fermentation were carried out at the optimum temperature of E.coli growth which is 37 OC for 72 hours. The results of HPLC analysis showed that increase in fermentation time will increase succinic acid production. The maximum production of succinic acid is at pH 6.0. Initial substrate concentration (5 to 15 g/L) will increase Succinic acid production, but after 15 g/L substrate concentration, the succinic acid production will decrease. From this study, it was observed that the substrate concentration and pH are important factor that affects both growth and growth-associated productions of molecules to increased succinic acid production.